(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article about the language and religion as spheres of spiritual culture. Language and religion are the fundamental factors that determine the national mentality and form the national, linguistic, and religious pictures of the world of different peoples. Religion as a specific worldview belongs to human society throughout the world. Much of its history and religious beliefs are shared by most people today.